ANALISA POTENSI KECURANGAN PADA PRAKTIK BELANJA ONLINE - Selfiani Selfiani; Hendi Prihanto; Tri Yulaeli; Hermanto Jusuf Moestopo (Universitas Prof. Dr. Moestopo (Beragama), 2022)
The research was conducted with the aim of testing the effect of payment systems, ordering systems, and delivery systems on online shopping fraud. The sampling method is carried out using the snowball method or sampling which is getting bigger with each withdrawal because it gets references from respondents. The data for this study were obtained from people who use a number of online shopping sites in the Depok area, which were obtained with a total of 100 respondents from various circles. The observation period was carried out from August 2020 to February 2021 on a number of respondents who often use online shopping sites such as: Bukalapak, Lazada, Shopee, Tokopedia, Akulaku and so on. The analysis technique used is multiple regression with SPSS tools through validity and reliability tests before testing the hypothesis. The results of the study concluded that the payment system used, the ordering system, and the delivery system had a significant positive effect on the potential for online shopping fraud. aims to identify and analyze the occurrence of fraud on online shopping sites that are predicted to occur through payment system factors, ordering systems, and delivery systems on a number of online shopping sites observed in this study.